FUTURE DIRECTIONS FOR ENSURING ENVIRONMENTAL SUSTAINABILITY IN UZBEKISTAN - Karimjanova Dilnoza Komiljon kizi (European Science Publishing, 2025)
The future of environmental sustainability in Uzbekistan is a pressing concern that requires immediate attention and action. As the nation grapples with various environmental challenges, including water scarcity, land degradation, and pollution, it is imperative to develop strategic initiatives that ensure a sustainable future. This article explores potential directions that Uzbekistan can take to promote environmental sustainability, highlighting key areas such as policy reform, renewable energy adoption, conservation efforts, and public awareness.
Keywords: Environmental Sustainability, Uzbekistan, Renewable Energy, Policy Reform, Conservation, Climate Change, Water Management, Pollution Control.